Meningkatkan Hasil Belajar Matematika melalui Pembelajaran Team Assisted Individual Siswa Kelas VII-1 SMP 32 Pekanbaru - P. Poritas (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
As a mathematics teacher who taught class VII at SMP N 32 Pekanbaru. Researchers feel responsible for students' failures in learning. In class VII-1 where researchers teach, there are problems that need to be resolved, including the activities and student learning outcomes of mathematics that are very low. Some students are passive and do not want to ask if they have difficulty in learning mathematics. The students scores who reach KKM ≥ 80 is 43.8%. Based on these problems, it is necessary to improve the activities and mathematics learning outcomes of students through the cooperative learning model type Team Assisted Individualization Class VII-1 SMP N 32 Pekanbaru in 2018. The research method used is Classroom Action Research. Activities carried out include planning, implementation, observation, and reflection. The activity data is collected through observations at the end of each cycle. Data analysis using qualitative and quantitative. The results of Classroom Action research, namely from the learning outcomes in the first cycle students who complete learning from meetings 1, 2 and 3 on average are 66.7% in the second cycle increased to 87.1% up by 20.4% Learning incompleteness students are due to their lack of concrete abilities, therefore need guidance and attention from the teacher, from these results indicate that indicators of learning outcomes 75% of students who get a value of 80 have been reached in cycle 2.